The association of lipid-lowering therapy and blood pressure control among outpatients with hypertension at the Felege Hiwot Comprehensive Specialized Hospital, Northwest Ethiopia - Abebe, Rahel Belete; Kebede, Sewnet Adem; Birarra, Mequanent Kassa (Frontiers in Cardiovascular Medicine, 2023)
Abstract: Background: The lipid lowering medications known as statins have been shown in controlled clinical trials to have pleiotropic properties, such as lowering blood pressure, in addition to lowering cholesterol levels. The purpose of this study was to see if there was a possible link between blood pressure control and statin therapy in hypertensive outpatients in a real clinical setting. Patients and methods: A retrospective comparative cohort study of 404 hypertensive patients was carried out. A systematic random sampling technique was used. For data entry, Epi-Data version 4.6 was used, and SPSS version 25 was used for further analysis. For group comparisons, chi square and independent t-tests were computed. To determine the relationship between statin use and blood pressure control, a binary logistic regression model was employed. To declare statistical significance, a 95 % confidence interval and a P-value of <0.05 were used. Results: Half of the study participants who were using a prescribed statin were assigned in the statin group whereas the remaining participants who don’t take statins were used as control group. After three months of statin treatment, BP control to <130/80mmHg was significantly greater (P = 0.022) in the statin group (52.5 %) in comparison to the control group (41.0%). Use of statin raises the likelihood of having the blood pressure under control by 1.58 times when compared to statin non-users. After controlling for possible confounders statin therapy still increased the odds of having controlled BP by a factor of 5.98 [OR=5.98; 95 % CI; 2.77-12.92]. Conclusion:The study revealed that blood pressure control was higher among statin user hypertensive patients. Favorable effects of statin use were independently observed, even after correction for age, presence of dyslipidemia and duration of antihypertensive therapy. Therefore the importance of concomitantly added lipid lowering drugs like statins and their role in managing poor blood pressure control should be given due emphasis.